Youth Participation in Rutong Village Development Programme: A Character Development Study - Salis, M. Rizkoni; Abdin, Maslan; Maitimu, Nexsien Richard (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2025)
Robust positive character traits are crucial for cultivating a responsible and integrity-oriented generation. The development of character among youth is pivotal in addressing global challenges. Their active involvement in village development, in accordance with Law Number 6 of 2014, is crucial for the success of such programmes. Youth participation not only benefits the village but also enhances their sense of responsibility, social awareness, and skills. In Rutong Village, Ambon, young people play a significant role in development programmes aimed at improving their quality of life and shaping their character. This research intends to evaluate youth involvement in village development initiatives, the challenges faced, and the analysis of character development. A quantitative descriptive method was employed to understand youth participation and its impact on their character development. The results indicate that the average participation score of youth is 3.30 with a standard deviation of 1.10, reflecting a neutral or hesitant attitude towards their involvement. Several barriers encountered include a lack of time, information, family support, facilities, and engagement in programmes. Meanwhile, the average score of 3.84 with a standard deviation of 0.93 indicates approval of character formation and their moral values.